2021
DOI: 10.1002/aenm.202102559
|View full text |Cite
|
Sign up to set email alerts
|

π‐Extended Conjugated Polymer Acceptor Containing Thienylene–Vinylene–Thienylene Unit for High‐Performance Thick‐Film All‐Polymer Solar Cells with Superior Long‐Term Stability

Abstract: Despite the rapid developments in all‐polymer solar cells (all‐PSCs) due to the progress of polymerized small molecular acceptors (PSMA), the effect of linkage unit conjugation on the polymer acceptor (PA) is not well understood and PAs with high efficiency, good stability, and thickness‐insensitivity are rarely seen. Herein, two novel PSMAs, named PJTVT and PJTET are designed, by incorporating conjugated thienylene‐vinylene‐thienylene (TVT) and unconjugated thienylene–ethyl–thienylene (TET) units, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 54 publications
4
89
0
Order By: Relevance
“…As the development of molecular structure design and device processing continues, all-polymer solar cells (all-PSCs) have attracted more and more attention, especially in the study of device stability. [1,2] Bulk heterojunction (BHJ) all-PSCs use processing [30,31] with two different solvents can be achieved in all-PSCs. The donor and acceptor are deposited sequentially from two orthogonal solvents, and the lower layer will not be damaged by the solvent used for the upper layer during its spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…As the development of molecular structure design and device processing continues, all-polymer solar cells (all-PSCs) have attracted more and more attention, especially in the study of device stability. [1,2] Bulk heterojunction (BHJ) all-PSCs use processing [30,31] with two different solvents can be achieved in all-PSCs. The donor and acceptor are deposited sequentially from two orthogonal solvents, and the lower layer will not be damaged by the solvent used for the upper layer during its spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PM6:PY-V-γ demonstrates a more balanced μ h /μ e ratio, which facilitates the charge extraction and collection, thus the best FF among the devices. [61] To correlate the charge transport properties with the morphology of the blends, grazing incidence wide-angle X-ray scattering (GIWAXS) experiments were conducted to investigate the morphology features of the pristine and blend films. [62] As shown in Figure S8 (Supporting Information), the (010) peaks of the pristine PY-V-γ, PY-T-γ, and PY-2T-γ films appeared at q z ≈ 1.62 Å -1 , demonstrating preferential face-on orientation.…”
Section: Resultsmentioning
confidence: 99%
“…99 Very recently, Huang et al reported a polymer acceptor named PJTVT, which contains the hienylene–vinylene–thienylene (TVT) unit. 100 The devices of JD40: PJTVT showed a PCE of 16.13% as well as superior thickness-insensitivity and long-term stability. Huang et al synthesized a narrow-band-gap polymer acceptor PJ1 via linking the SMA building block TTPBT-IC.…”
Section: The Development Of New Donor and Acceptor Materials In The Oscsmentioning
confidence: 93%